2008
DOI: 10.1016/j.jmb.2007.05.058
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Mechanical Unfolding of RNA Pseudoknots

Abstract: The pseudoknot is an important RNA structural element that provides an excellent model system for studying the contributions of tertiary interactions to RNA stability and to folding kinetics. RNA pseudoknots are also of interest because of their key role in the control of ribosomal frameshifting by viral RNAs. Their mechanical properties are directly relevant to their unfolding by ribosomes during translation. We have used optical tweezers to study the kinetics and thermodynamics of mechanical unfolding and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
127
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(138 citation statements)
references
References 63 publications
7
127
1
2
Order By: Relevance
“…Virus and three different mutants showed no general correlation between mechanical properties of unfolding and the variations in frameshifting efficiency (26). However, this second study revealed that at close to 24 pN of force, the frameshifting pseudoknots exhibited an inversely proportional relationship between frameshifting efficiency and the rate constants of unfolding (26).…”
Section: Introductionmentioning
confidence: 76%
See 4 more Smart Citations
“…Virus and three different mutants showed no general correlation between mechanical properties of unfolding and the variations in frameshifting efficiency (26). However, this second study revealed that at close to 24 pN of force, the frameshifting pseudoknots exhibited an inversely proportional relationship between frameshifting efficiency and the rate constants of unfolding (26).…”
Section: Introductionmentioning
confidence: 76%
“…However, this second study revealed that at close to 24 pN of force, the frameshifting pseudoknots exhibited an inversely proportional relationship between frameshifting efficiency and the rate constants of unfolding (26).…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations